Particulate and solubilized β-glucan and non-β-glucan fractions of Euglena gracilis induce pro- and anti-inflammatory innate immune cell responses and exhibit antioxidant properties - Phillips FC; Jensen GS; Showman L; Tonda R; Horst G; Levine R (Dove Medical Press, 2019)
Farrah C Phillips,1,* Gitte S Jensen,2 Lucas Showman,3 Rachel Tonda,1 Geoff Horst,4 Robert Levine4,* 1Kemin Industries, Animal Nutrition and Health of North America, Des Moines, IA 50317, USA; 2NIS Labs, Klamath Falls, OR 97601, USA; 3W.M. Keck Metabolomics Research Laboratory, Iowa State University, Ames, IA, USA; 4Kemin Industries, Plymouth, MI 48170, USA *These authors contributed equally to this work Purpose: The purpose of this work was to determine the pro- and anti-inflammatory properties of the single-cell organism Euglena gracilis (EG) and various fractions of its whole biomass.Methods: Heterotrophically grown EG was tested, along with its aqueous fraction (E-AQ), the intact linear β-glucan paramylon granules (PAR), and alkaline-solubilized paramylon. Peripheral blood mononuclear cell cultures were treated with the test products and analyzed for a variety of cellular responses. Immune cell activation was evaluated by flow cytometry detection of CD69 levels on CD3−CD56+ NK cells, CD3+CD56+ NKT cells, and monocytes, and cytokines were analyzed from the cell culture supernatants. Antioxidant capacity was measured by Folin–Ciocalteu assay and cellular antioxidant protection and MTT assays.Results: EG and E-AQ were the most effective in driving immune cell responses as measured by CD69 upregulation on NK and NKT cells and proinflammatory (tumor necrosis factor, IL-6, IL-1β) cytokine production. None of the test products effectively stimulated monocyte. EG and PAR inhibited reactive oxygen species under conditions of oxidative stress. E-AQ contained antioxidants capable of providing cellular antioxidant protection from oxidative damage and protection of mitochondrial function under inflammatory conditions.Conclusion: The effects of EG on immune function are only partially attributable to the content of the β-glucan, paramylon. The regulation of additional cellular responses, such a reactive oxygen species production and resistance to oxidative stress, is likely mediated by currently unknown molecules found in the EG cell. Keywords: CAP-e, oxidative stress, PAMP, Dectin-1, paramylon, mannitol